Efektivitas Proses Oriented Guided Inquiry Learning (Pogil) Berbasis Isu Sosiosaintifik (Ssi) Terhadap Kemampuan Berpikir Kritis Siswa - Lisa Utami (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
The implementation of discussion in learning activities based on problem in schools could improve students' critical thinking skills. However, in its implementation, there were still several problems, one of them was the lack of students' ability in solving the problems. So, there needs to be a learning model that could create the learning based on problem. This research aimed at knowing 1) difference of students' critical thinking abilities, 2) the effectiveness of learning using POGIL model based on SSI students' critical thinking skills. This research was conducted in the even semester of 2021/2022 Academic Year at X MIPA grade of Senior High School Taruna Mandiri Pekanbaru on electrolyte and non-electrolyte solutions materials. It was an experimental research with pretest and posttest nonequivalent control group design. T-test (knowing difference of students' critical thinking abilities) and N-gain test (knowing the level of effectiveness) were used for analyzing the data. The results of this research showed that 1) there was a difference of students' critical thinking skills between the experiment and control groups, the posttest average scores of critical thinking skills in the experiment group was 82.00 and the control group was 75.21, the result of t-test obtained that a significance value was 0.002 < 0.05, so that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. 2) Learning using the POGIL (Process Oriented Guided Inquiry Learning) model was effective on students' critical thinking skills. The N-gain value of the experimental group from each student: there were 28 students in the high N-gain category (93.33%) and 2 students in the medium N-gain category (6.67%) who were into the effective category. The conclusion was learning using the POGIL (Process Oriented Guided Inquiry Learning) model was effective on students' critical thinking skills.